Comparing the differences of characteristic flavour between natural maturation and starter culture for Mucor‐type Douchi. (19th March 2016) - He, Guiqiang; Huang, Jun; Liang, Ru; Wu, Chongde; Zhou, Rongqing
Summary: In this research, effects of maturation times on volatiles of Mucor ‐ type Douchi were investigated. Results showed that 2‐year matured sample exhibited higher concentrations of characteristic flavours including alcohols, esters, phenols, ketones and pyrazines. Additionally, effects of starter cultures addition on volatiles were investigated, and results demonstrated that inoculated fermented samples presented higher amounts of aldehydes, ketones, phenols and pyrazines compared with that of naturally fermented sample. Analysis of odour activity value (OAV) suggested that increased OAVs of eight compounds that mainly contributed to the flavour of Douchi ranged from onefold to 6.5‐fold in the Tetragenococcus halophilus, Zygosaccharomyces rouxii and Candida versatilis co‐cultured sample. Furtherly, by comparing the characteristic flavour of co‐cultured and 2‐year matured samples, no significant difference was observed in the OAV of flavour except rose‐like and soapy flavour, which indicated that co‐culture of the three strains during Douchi fermentation may facilitate the formation of flavours and shorten the fermentation process. Abstract : In the present study, the effects of maturation times and starter cultures on volatile compounds of Mucor‐type Douchi were investigated. By comparing the characteristic flavour of co‐cultured and 2‐years matured samples, no significant difference was observed in the OAV of characteristic flavour except rose‐like and soapy flavour among these samples. These findings revealed that the co‐culture of the Tetragenococcus halophilus, Zygosaccharomyces rouxii and Candida versatilis during Douchi fermentation may promote the formation of characteristic flavour and shorten the process.